Inception and utility of a renal replacement registry using administrative health data in North‐East Italy. Issue 2 (18th January 2017) - Valent, Francesca; Busolin, Anna; Boscutti, Giuliano
SUMMARY: Background: Disease registries are useful tools for public health planning, evaluating clinical practice and providing information on cohorts of patients. Methods: The administrative databases of the regional health information system of Friuli Venezia Giulia, Italy were used to build a regional registry of the resident population in renal replacement therapy (including dialysis and renal transplantation), through an algorithm taking into account hospital discharge and outpatient ambulatory care data. The registry includes an anonymous univocal identifier, the start date for the replacement therapy and changes of status (haemodialysis, peritoneal dialysis, renal transplantation). Data from the registry were used to estimate incidence rate, prevalence and mortality of patients receiving renal replacement therapy in 2014. In addition, we described an example of how the registry can be used to assess the prevalence of selected comorbidities. Results: In Friuli Venezia Giulia in 2014, we estimated an incidence rate of renal replacement therapy of 166 per million inhabitants and a prevalence of 1, 400 per million inhabitants. A total of 10% of the patients died in the study year. Hypertension, heart disease and diabetes mellitus were common co‐morbidities. Conclusion: The registry allows us to estimate the incidence rate and prevalence of renal replacement therapy and also to investigate specific issues regarding these patients through record linkage with other administrative health databases.